An improved collagen zymography approach for evaluating the collagenases MMP-1, MMP-8, and MMP-13 - Seniz Inanc; Didem Keles; Gulgun Oktay (BioTechniques, 2017)
Collagen zymography is an SDS-PAGE–based method for detecting both the proenzyme and active forms of collagenases. Although collagen zymography is used for assessment of the matrix metalloproteinases MMP-1 and MMP-13, it can be difficult to detect these collagenases due to technical issues. Moreover, it remains unclear whether the collagenase activity of MMP-8 can be detected by this method. Here, we present an improved collagen zymography method that allows quantification of the activities of MMP-1, MMP-8, and MMP-13. Activities of recombinant collagenases could be detected in collagen zymogram gels copolymerized with 0.3 mg/mL type I collagen extracted from rat tail tendon. This improved method is sensitive enough to detect the activity of as little as 1 ng of collagenase. We generated standard curves for the three collagenases to quantify the collagenolytic activity levels of unknown samples. To validate our improved method, we investigated MMP-1 activity levels in human thyroid cancer (8505C) and normal thyroid (Nthy-ori-3–1) cell lines, finding that the proenzyme and active MMP-1 levels were greater in 8505C cells than in Nthy-ori-3–1 cells. Taken together, our data show that collagen zymography can be used in both molecular and clinical investigations to evaluate collagenase activities in various pathological conditions.